2008
DOI: 10.1007/s00436-008-1004-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neem extract against the blowfly and housefly

Abstract: The blowfly, Chrysomya megacephala (Fabricius), and housefly, Musca domestica Linnaeus, are ubiquitous insects that have the potential to spread a variety of pathogens to humans and livestock. Pest management techniques for populations of these flies are needed. Currently, bioinsecticides, particularly those derived from plant origin, have been increasingly evaluated in controlling populations of medically important insects. In this study, an attempt was made to evaluate the efficacy and biological activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
2
17
0
3
Order By: Relevance
“…Against larval housefl ies, the LC 50 and LC 90 were 10.5 and 20.2 ppm, respectively. Laboratory tests showed that neem products containing 0.24 % azadirachtin A signifi cantly reduced larval and pupal survival, adult emergence, pupal weight, adult wing length and fecundity on the subsequent generation, in a dose-dependent manner in housefl y, Musca domestica , and blowfl y, Chrysomya megacephala (Siriwattanarungsee et al 2008 ). The data reinforced the effi cacy of neem extract in reduced adult emergence and anti-fecundity in the subsequent generation.…”
Section: Insect Growth-regulating/larvicidal Activitiessupporting
confidence: 72%
“…Against larval housefl ies, the LC 50 and LC 90 were 10.5 and 20.2 ppm, respectively. Laboratory tests showed that neem products containing 0.24 % azadirachtin A signifi cantly reduced larval and pupal survival, adult emergence, pupal weight, adult wing length and fecundity on the subsequent generation, in a dose-dependent manner in housefl y, Musca domestica , and blowfl y, Chrysomya megacephala (Siriwattanarungsee et al 2008 ). The data reinforced the effi cacy of neem extract in reduced adult emergence and anti-fecundity in the subsequent generation.…”
Section: Insect Growth-regulating/larvicidal Activitiessupporting
confidence: 72%
“…Although synthetic insecticides could help to manage house flies, some side effects to the environment and development of insecticide resistance in house flies [21,22] focus on the need to explore alternative insecticides. A. indica essential oils have insecticidal potential and used previously to manage house flies and other pests in different parts of the world [23]. Sound knowledge of plants in community health could be very helpful particularly in cases where mainstream health care is often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This secondary metabolite is known to be effective against a wide range of insect pests as well as vectors (Su and Mulla 1999;Rong et al 2000;Huang et al 2004;Sriwattanarungsee et al 2008), and its efficacy against the mosquito targets has been proven by its ovicidal (Su and Mulla 1999), larvicidal, and pupicidal activity (Coria et al 2008) and inhibition of insect growth (Okumu et al 2007). Despite these merits, there are, however, at least two notable disadvantages with azadirachtin: it degrades rapidly upon exposure to sunlight, resulting in great loss of its insecticidal activity (Johnson et al 2003), and azadirachtin (0.5 and 1 ppm) in water suspension enhances the oviposition response of the mosquito Culex tarsalis, and this enhancement was more pronounced in 1-week-old neem formulation (Su and Mulla 1999).…”
Section: Introductionmentioning
confidence: 97%